(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Thereis general agreement that instruction in the L1 is beneficial and that transferof literacy skills almost always occurs to the L2. However, the followingresearch studies looked at the question of how to deal with students whose L1skills were not in writtenlanguages or who have limited or no literacy skills in their L1 and wereattempting to acquire literacy skills in English.